Application of Shannon Weaver's Communication Model in Reducing Anxiety in the Elderly in the Parempuan Public Health Center Working Area, West Lombok District - Sukardin M.Siddik; Bq Nova Aprilia Azamti (Universitas Muhammadiyah Tangerang, 2019)
This study was a study of the application of Shannon Weaver's communication techniques in reducing anxiety in the elderly. The purpose of this study was to find out whether there was any influence in applying Shannon Weaver's communication model to Decrease of Anxiety Level in the Elderly in the Parempuan Public Health Center Working Area in West Lombok District.The method used was quasi-experimental with pre-post test design in one group (one-group pre-test-posttest design), the design of this study was to measure what happened in the experimental group according to the initial conditions before the experiment, and the apparent differences at the end of the experiment. The sample in this study was elderly who experienced anxiety in Public Health Center Working Area that fulfilled the inclusion criteria. The sampling technique used purposive sampling technique, and the data analysis was used t-test (paired test) statistical analysis.The results showed that before the Shannon Weaver communication model was given, respondents who experienced mild anxiety were 52 people (53.1%) and moderate anxiety were 46 respondents (46.9%). After being given the Shannon Weaver communication model there was a decrease in anxiety levels in the elderly, there were 39 respondents (39.8%) did not experience anxiety, mild anxiety as many as 35 respondents (35.7%), and respondents who experienced moderate anxiety as much as 24 (24, 5%).The results of the paired t-test statistical test obtained P = 001 which means P <0.05. The null hypothesis (HO) was rejected and the alternative hypothesis (Ha) was accepted so that, there was an influence of the application of the Shannon Weaver communication model to the decline in anxiety levels in the elderly in the Parempuan Public Health Center Working Area. So that Shannon weaver communication is effectively used to reduce anxiety levels in the elderly.